Comparison of Accumulated Degree-Days and Entomological Approaches in Post Mortem Interval Estimation - Lorenzo Franceschetti; Jennifer Pradelli; Fabiola Tuccia; Giorgia Giordani; Cristina Cattaneo; Stefano Vanin (Insects, 2021)
Establishing the post mortem interval (PMI) is a key component of every medicolegal death investigation. Several methods based on different approaches have been suggested to perform this estimation. Among them, two methods based their evaluation on the effect of the temperature and time on the considered parameters: total body score (TBS)/accumulated degree-days (ADDs) and insect development. In this work, the two methods were compared using the results of minPMI and PMI estimates of 30 forensic cases occurring in northern Italy. Species in the family Calliphoridae (Lucilia sericata, Calliphora vomitoria and Chrysomya albiceps) were considered in the analyses. The results highlighted the limits of the TBS/ADD method and the importance of the entomological approach, keeping in mind that the minPMI is evaluated. Due to the fact that the majority of the cases occurred in indoor conditions, further research must also be conducted on the different taxa to verify the possibility of increasing the accuracy of the minPIM estimation based on the entomological approach.